The Influence of Adversity Quotient on Career Adaptability among Internship Students at Universitas Islam Negeri Raden Fatah - Desti Agustin; Siti Dini Fakhriyah; Limisran Limisran (Jurnal Keilmuan Pendidikan, 2026)
Career adaptability is an essential competency for university students transitioning from higher education to the workplace, particularly during internships. However, previous studies examining the relationship between adversity quotient and career adaptability have reported inconsistent findings, while evidence among Indonesian internship students remains limited. This study aimed to examine the effect of adversity quotient on career adaptability among internship students at Universitas Islam Negeri Raden Fatah. A quantitative cross-sectional design was employed involving 392 internship students selected using purposive sampling. Data were collected using the Adversity Response Profile (ARP) adapted by Utomo (2021) and the Career Adapt-Abilities Scale (CAAS) adapted by Sulistiani et al. (2018). Simple linear regression was used to analyze the data. The results indicated that adversity quotient had a positive and significant effect on career adaptability (R = .893, R² = .797, F = 1527.450, p < .001), explaining 79.7% of the variance in career adaptability. These findings highlight the importance of adversity quotient as a psychological resource that supports students' career adaptability during internships and provide empirical evidence for developing university career preparation and internship support programs.